ENGLISH INTRODUCTION THROUGH DIGITAL STORYTELLING IN EARLY CHILDHOOD - Gaya Tridinanti (IJLECR (International Journal of Language Education and Cultural Review), 2017)
The introduction of simple English sentences to early childhood is not an easy task. This is often a problem for teachers. The purpose of this study is to investigate the introduction of the English language by using a digital storytelling. This research is an action research. Subjects of research include 20 children from group B (5-6 years) of Happy Kids Kindergarten in Palembang. The finding shows that there is an enhancement  in pre-cycle is 33%, to 59% in Cycle I. In Cycle II is 79% and  in Cycle III is 97%. Thus, an increase of 26% from the pre-cycle to cycle I. Increased 20% from Cycle I to Cycle II and increased 18% from Cycle II to Cycle III. The result of the English introduction action through digital storytelling in early childhood shows a significant percentage increase from cycle I to cycle II, and cycle III. The increase in percentage indicates that the use of digital storytelling can improve the process and the results of early childhood English introduction in terms of meaning, show, imitate, and say simple English sentences Therefore, digital storytelling based learning can be incorporated in the curriculum of Kindergarten.